Development Strategy of Industrial Insurance in Russia: the rationale and the formation - N. P. Sakhirova (Путеводитель предпринимателя, 2020)
When covering economic conditions strengthen the insurance mechanism on the stability of the industry and proved the key areas of the Strategy of development of industrial insurance in Russia.